The Level of Emotional Regulations among a Sample of Secondary School Students in Jeddah and it’s Relation with Life Satisfaction - Al-Sulami, Safiah Mohammed; Akram, Hadeel Abdullah (Journal of Educational and Psychological Sciences, 2020)
This study aims to explore the level of both the emotional regulation, the life satisfaction, and the correlation relationship between them as main variables, in addition, to identify the variance between them according to the two variables (class and the specialization), The psychometric features and the appropriateness of the study tools were insured. The main sample of the study consisted of (231) female student. The study found out that the study sample has an average level of emotional regulation and a high level of life satisfaction. In addition, it showed a positive relationship with statistically significant between the emotional regulation and the life satisfaction, it also showed a statistically significant difference in the total degree of the life satisfaction which refers to the impact of specialization variable in favor of the literacy specialization. Based on these findings, the study presented some of the recommendations to the educational institutions and to the responsible of the counseling process in the education schools, hoping to contribute in the development of the presented counseling services to the students of the secondary stage.